On Islamic da‘wah and sustainable development - Bensaid, Benaouda (IDOSI, 2013)
Rethinking the development of Islamic da‘wah according to the perspective of development is understandable in view of today’s global preoccupation with the problems and challenges of sustainability. This paper seeks to explore the relationship of Islamic da‘wah with the themes and concerns of sustainability, granting special attention to the position taken by da‘wah on sustainable development while further highlighting converging issues between da‘wah and development such as the building of human capital, synergistic cooperation, planning and effectiveness. This study addresses and explores relatively new dimensions of da‘wah development which highlight the critical need for capitalizing on the religious, spiritual and moral reform of communities as an effective means to actualizing the agenda of sustainable development. This study raises interesting questions pertaining to the weight given to development and sustainability in the contemporary Islamic discourse of reform and the indicators and measures for religious development of humans and societies, in addition to the potential for conclusive growth of sustainability through complementary da‘wah configurations.